2023
DOI: 10.1021/acs.inorgchem.2c04364
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Catalytic Performance of MOF-808(Zr) by Direct Generation of Rich Defective Zr Nodes via a Solvent-Free Approach

Abstract: Creation of rich open metal sites (defect) on the nodes of metal−organic frameworks (MOFs) is an efficient approach to enhance their catalytic performance in heterogeneous reactions; however, direct generation of such defects remains challenging. In this contribution, we developed an in situ green route for rapid fabrication of defective MOF-808(Zr) with rich Zr-OH/OH 2 sites (occupying 25% Zr coordination sites) and hierarchical porosity without the assistance of formic acid and solvent. The optimal MOF-808(Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“… The results showed that the catalysts with different morphologies and Ce content showed similar carbon structures. Studies have shown that the presence of both defective carbon and graphitized carbon plays a significant role in improving electrochemical performance by fine-tuning the local electronic and geometric characteristics in the carbon matrix . Additionally, the FeCe-SAD/HPNC catalyst was in a moderate-intensity graphitization, which was conducive to improving the catalytic performance of the ORR.…”
Section: Resultsmentioning
confidence: 99%
“… The results showed that the catalysts with different morphologies and Ce content showed similar carbon structures. Studies have shown that the presence of both defective carbon and graphitized carbon plays a significant role in improving electrochemical performance by fine-tuning the local electronic and geometric characteristics in the carbon matrix . Additionally, the FeCe-SAD/HPNC catalyst was in a moderate-intensity graphitization, which was conducive to improving the catalytic performance of the ORR.…”
Section: Resultsmentioning
confidence: 99%
“…However, when DMSO is added, the desulfurization efficiency is completely inhibited. Therefore, it can be inferred that · OH radicals might be the major active intermediates during the ODS reaction . In order to prove this assumption, ESR spectroscopy with the existence of the radical trapping reagent 5,5-dimethyl-1-pyrroline- N -oxide (DMPO) was conducted (Figure b) .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be inferred that • OH radicals might be the major active intermediates during the ODS reaction. 63 In order to prove this assumption, ESR spectroscopy with the existence of the radical trapping reagent 5,5-dimethyl-1pyrroline-N-oxide (DMPO) was conducted (Figure 6b). 64 It is worth noticing that no free radical signal is detected without YS-V O -NMO, while a strong fourfold peak signal belonging to DMPO− • OH is observed after 1 h of reaction with the presence of the catalyst.…”
Section: Catalytic Ods Performancementioning
confidence: 99%
“…[18][19][20] The random long-range networks in the amorphous phase provide ample isotropic ion diffusion routes and large numbers of active sites (defects/vacancies) that enhance the ion-intercalation pseudocapacitance of the material. [16] Furthermore, the loose structure of amorphous materials usually accommodates small lattice distortion and volume expansion during cation insertion/extraction, which enhances the cycling stability. [19,21] Unfortunately, to our knowledge, amorphization engineering for multi-ion storage has not been reported.…”
Section: Introductionmentioning
confidence: 99%